Analysis Of The Implementation Of Quality Management Of Employee Performance And Organizational Culture - Asep Hidayat; Radifa Ruli; Rasya Firrizqy; Muhamad Gimbastian; Moh. Ilham Ramadhan; Naufal Lathif; Rayhan Yanuar; Fachri Syarifudin; Muh. Ramadhan Mahendra (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study investigates the relationship between quality management implementation and its impact on employee performance and organizational culture. Through the use of a holistic analytical methodology, the study results show that effective implementation of quality management principles contributes to significant improvements in productivity and quality of employee performance. The findings also highlight the crucial role of quality management in shaping an adaptive, collaborative, and innovation- oriented organizational culture. The implication is that good quality management implementation can provide a strong foundation for organizational growth through improved individual performance and the establishment of an inclusive corporate identity.